The Influence of COVID-19 on Air Quality in India: A Boon or Inutile - Gautam, Sneha (Bulletin of environmental contamination and toxicology, 2020)
Corona virus diseases-2019 (COVID-19), an infectious disease identified in late December, 2019, in Wuhan city of China, was declared a pandemic by the World Health Organization. Most countries including India have announced some sort of lockdown to reduce the effects of COVID-19 and discontinue the transmission of novel coronavirus. Major negative effects on the social and surrounding environment have been reported due to COVID-19, however positive effects have also been observed with respect to air quality. Secondary results have been taken from National Aeronautics and Space Administration (NASA), indicating significant reduction (50%) in air quality of Indian region. This perspective highlights the effects of the lockdown due to COVID-19 on aerosol optical thickness specifically in India.